2008
DOI: 10.1007/s00167-008-0662-3
|View full text |Cite
|
Sign up to set email alerts
|

Staged bilateral mobile-bearing and fixed-bearing total knee arthroplasty in the same patients: a prospective comparison of a posterior-stabilized prosthesis

Abstract: Mobile-bearing total knee arthroplasty (TKA) has several theoretical advantages over fixed-bearing TKA. We conducted a prospective randomized trial to compare the results of mobile-bearing and fixed-bearing posterior-stabilized TKA in the same patients using the same femoral component design of a mobile-bearing prosthesis in one knee and a fixed-bearing prosthesis in the other knee in 25 patients with osteoarthritis. The mean follow-up was 40 months. No significant differences were found in the mobile-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…In total knee replacement (TKR) surgery, mobile bearing (MB) prostheses facilitate planar rotation about the vertical axis of the tibia [1] and [2], with a view to reducing sub-surface stress through dual surface articulation at both the superior and inferior surfaces of a polyethylene insert [3] and [4]. Dual surface articulation promotes load sharing between the relative displacements of the tibial and femoral components, dissipating knee moments and shear forces to the surrounding soft tissues in a similar manner to the normal knee [5].…”
Section: Introductionmentioning
confidence: 99%
“…In total knee replacement (TKR) surgery, mobile bearing (MB) prostheses facilitate planar rotation about the vertical axis of the tibia [1] and [2], with a view to reducing sub-surface stress through dual surface articulation at both the superior and inferior surfaces of a polyethylene insert [3] and [4]. Dual surface articulation promotes load sharing between the relative displacements of the tibial and femoral components, dissipating knee moments and shear forces to the surrounding soft tissues in a similar manner to the normal knee [5].…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have specifically compared fixed-bearing posterior-stabilized and mobile-bearing posterior-stabilized total knee prostheses. In a small number of studies, no differences in midterm functional and radiographic outcomes between patients with fixed and those with mobile-bearing posteriorstabilized prostheses were identified 4,11,12 . In one study with limited follow-up, implant survival rates were also reported to be similar 14 .…”
mentioning
confidence: 96%
“…Mobile bearings were introduced in an attempt to reduce polyethylene wear and possibly reduce torque at the bone-implant interface. In biomechanical testing, mobile bearings were found to reduce both contact stress and polyethylene wear; this has the potential to decrease the risk of revision, particularly in younger and more active patients [3][4][5][6][7] . It has also been argued that mobile bearings have the potential to enhance patellar tracking, reduce pain, enhance function, and reduce patellofemoral-related revision 8 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of bilateral TKR with different prostheses in the same patient have compared mobile versus fixed-bearing models, [2][3][4] standard versus highflex models, 5 and standard versus gender-specific models. 6 Patellar clunk syndrome has been reported in different models, especially in posterior-stabilised prostheses.…”
Section: Discussionmentioning
confidence: 99%